Equivalent Modal Damping Ratios of a Composite Tube-Type Tall Building to Dynamic Wind Loading. (1996) - Huang, B.C.; Lam, K.M.; Leung, A.Y.T.; Cheung, Y.K.
Abstract : This article discusses computing methods of the equivalent modal damping ratio for a composite tube-type tall building. The equivalent damping ratio of a composite structure under wind-induced vibrations encompasses the combined effects from the different values of damping, mass, and stiffness of the external and internal tubes. A detailed method incorporating Rayleigh damping and the transfer matrix method is proposed for the determination of the equivalent modal damping ratio. A simplified method for engineering applications is also proposed. Results for a 40-story building are presented exemplifying the computation and relationships between the properties of the external and internal tubes.